2018
DOI: 10.1021/acs.jpcc.8b09287
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Study of Descriptors for Oxygen Evolution Reaction Catalysis in Perovskite Oxides

Abstract: Ever proposed descriptors of catalytic activity for oxygen evolution reaction (OER) were systematically investigated. A wide variety of stoichiometric perovskite oxides ABO 3 (A = Ca, Sr, Y, La; B = Ti, V, Cr, Mn, Fe, Co, Ni, Cu) were examined as OER catalysts. The simplest descriptor, e g electron number of transition metal ion at B-site, was not applicable for OER overpotentials (η) of the compounds tested in this study. Another descriptor, oxygen 2p band center relative to Fermi energy (ε 2p), was not neces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
113
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(124 citation statements)
references
References 48 publications
(132 reference statements)
11
113
0
Order By: Relevance
“…This is a good indication of the improved OER kinetics on the perovskite catalyst incorporating silicon because catalysts having a smaller Tafel slope tend to deliver significantly increased currents at only moderate increments of overpotential. A detailed comparison with literature results, as tabulated in Supplementary Table 4, suggests that the Si-incorporated Si-SCO catalyst compares favourably to the state-of-the-art perovskite catalysts such as BSCF, PBC and SNCF, among many others [7][8][9][10][11][12][13]18,19,31,[42][43][44][45][46][47] .…”
Section: Resultsmentioning
confidence: 92%
“…This is a good indication of the improved OER kinetics on the perovskite catalyst incorporating silicon because catalysts having a smaller Tafel slope tend to deliver significantly increased currents at only moderate increments of overpotential. A detailed comparison with literature results, as tabulated in Supplementary Table 4, suggests that the Si-incorporated Si-SCO catalyst compares favourably to the state-of-the-art perovskite catalysts such as BSCF, PBC and SNCF, among many others [7][8][9][10][11][12][13]18,19,31,[42][43][44][45][46][47] .…”
Section: Resultsmentioning
confidence: 92%
“…Further studies showed a strong correlation between OER activity and oxygen p‐band center relative to the Fermi level through theoretical calculations [26] . Other parameters, including cations in octahedral sites and transition metal 3d – O 2p hybridization, have been widely studied by metal doping or partial element substitution [27–30] . Surface reconstruction mediated by transition metals has been reported to form active reaction sites, such as oxyhydroxide sites on the catalyst interface [31,32] .…”
Section: Introductionmentioning
confidence: 99%
“…Recent experimental results and theoretical studies pointed out that increasing the transition metal-oxygen bond covalency leads to an enhanced OER kinetics concomitant with the destabilization of the surface [12][13][14][15][16][17][18] . Screening a large variety of transition metal oxides, it could be shown that this phenomenon is related to the relative position of the Fermi level when compared to the reversible potential for water oxidation, as well as to the charge-transfer energy [19][20][21][22] . In short, lowering the charge-transfer energy triggers the redox activity of oxygen ligand, leading to the involvement of lattice oxygen into the OER following the so-called lattice oxygen evolution mechanism.…”
mentioning
confidence: 99%